ASSESSING ICHTHYOFAUNAL DIVERSITY OF DAL AND MANASBAL LAKES, KASHMIR VALLEY - GUL, SOBIYA; ABUBAKR, ADNAN; SHAH, TASADUQ HUSSAIN; BHAT, FAROOZ AHMAD; AMIN, ADNAN; RASHID , IFRAH (Journal of the Inland Fisheries Society of India, 2026)
This study investigates the ichthyofaunal diversity of Dal and Manasbal Lakes, located in the Kashmir Valley. Over the course of a year, sampling was conducted to assess the fish diversity in these two water bodies. The findings revealed a total of seven fish species inhabiting both lakes, including indigenous and exotic varieties. However, the decline in the number of fish species in Dal Lake and Manasbal Lake was observed and attributed primarily to anthropogenic pressures such as pollution, habitat degradation, and the introduction of invasive species. Factors such as overfishing and habitat destruction further threaten the delicate balance of these aquatic ecosystems. Urgent conservation measures are imperative to mitigate the ongoing decline and restore the ecological integrity of Dal and Manasbal Lakes. This study underscores the importance of preserving aquatic biodiversity and highlights the need for collaborative efforts among conservationists to safeguard these invaluable natural treasures for future generations.